Духовність і відповідальність як умова відродження й ефективного розвитку України - Пономарьов, Олександр Семенович (НТУ "ХПІ", 2017)
Протягом тривалого часу Україна переживає глибоку системну кризу. Вона охопила суспільно-політичну, соціально-економічну і духовно-культурну сфери життя соціуму. Ця криза серйозно гальмує інноваційний розвиток країни. Основна її причина полягає у безвідповідальному ставленні широких верств населення до своїх суспільних обов’язків і навіть до свого життя і здоров’я. Одним з коренів такого стану є недостатня увага системи освіти до виховання й особистісного розвитку підростаючих поколінь та їх духовності і культури. Перш за все, це стосується формування у них почуття відповідальності й розвитку їхнього духовного світу.

For a long time, Ukraine is experiencing a deep systemic crisis. He embraced the socio-political, socio-economic and spiritual-cultural spheres of the life of the society. This crisis seriously hinders the country's innovative development. Its main reason is the irresponsible attitude of the broad strata of the population towards their public duties and even their own lives and health. One of the roots of this state is the insufficient attention of the education system to the upbringing and personal development of the younger generations, to their spirituality and culture. First of all, it concerns the formation of a sense of responsibility and development of their spirituality. This is the condition for the revival and ensuring the possibility of effective development of the country. Only in this way the educational system can successfully realize its social mission.
Spirituality and responsibility as the condition of revival and efficient development of Ukraine
Keywords: криза; завдання освіти; виховання; особистісний розвиток; crisis; tasks of education; personal development